2002
DOI: 10.1111/j.1542-474x.2002.tb00150.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Final Coronary Arterial Diameter After Coronary Angioplasty on Heart Rate Variability Responses

Abstract: Transient and rapidly recovered, especially parasympathetically modulated HRV reduction occurred after PTCA in patients with single-vessel disease. HRV reduction is associated with PTCA restenosis risk score and the degree of revascularization as invasive feature of angioplasty, hence it may be related to reperfusion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
14
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 31 publications
5
14
1
Order By: Relevance
“…The SDTS changes in HRV were consistent with the findings of Janowska-Kulinska et al [3], where SDTS changed from 27.2˘18.6 ms before PCI to 21.3˘32.8 ms after PCI (p = 0.044). The decrease of parasympathetic tone was also consistent with the findings of Kanadasi et al [9], who showed the parasympathetically modulated HRV reduction occurred after PCI procedure in patients with single-vessel disease. However, they were in opposition to the results reported by Tseng et al [15], where the HRV parameters recorded before PCI procedure did not differ significantly from those assessed directly after the PCI procedure.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…The SDTS changes in HRV were consistent with the findings of Janowska-Kulinska et al [3], where SDTS changed from 27.2˘18.6 ms before PCI to 21.3˘32.8 ms after PCI (p = 0.044). The decrease of parasympathetic tone was also consistent with the findings of Kanadasi et al [9], who showed the parasympathetically modulated HRV reduction occurred after PCI procedure in patients with single-vessel disease. However, they were in opposition to the results reported by Tseng et al [15], where the HRV parameters recorded before PCI procedure did not differ significantly from those assessed directly after the PCI procedure.…”
Section: Discussionsupporting
confidence: 80%
“…It has been shown that HRV indices decrease after a percutaneous coronary intervention (PCI) procedure [3] and this drop is accompanied by an increased sympathetic tone [9]. Studies have invariably demonstrated that coronary artery bypass grafting (CABG) also leads to significant HRV reduction [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…We speculate that the decrease in HRV parameters in early periods following recanalization of CTOs could be transient and might be associated with acute endothelial injury during the procedure or microembolization to the vascular bed that was previously protected from ischemia by collateral support. Consistent with the results of a previous study, localization of totally occluded coronary arteries in this study did not have significant impact on HRV results after the revascularization procedure [32]. Because the sinus node blood supply primarily comes from this artery, a significant change in HRV following successful PCI to RCA might be expected.…”
Section: Discussionsupporting
confidence: 90%
“…Parasympathetic indices are reduced in patients within 24 h after PCI (Tseng et al, 1996; Osterhues et al, 1998; Wennerblom et al, 2000; Kanadasi et al, 2002). However, this reduction in parasympathetic function appears to be a transient phenomenon (Osterhues et al, 1998; Kanadasi et al, 2002; Janowska-Kulińska et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…However, this reduction in parasympathetic function appears to be a transient phenomenon (Osterhues et al, 1998; Kanadasi et al, 2002; Janowska-Kulińska et al, 2009). In patients with greater than one target-vessel affected and/or with other comorbidities, HRV remains lower due to several factors (Tseng et al, 1996; Birand et al, 1998; Wennerblom et al, 2000; Kanadasi et al, 2002).…”
Section: Introductionmentioning
confidence: 99%